The Implementation of Daily Journal Writing in Teaching Recount Text for the Second Grade Students in MTs Khoirotul Islamiyah Pematangsiantar - Marhaeni KD Matondang (Budapest International Research and Critics University, 2020)
This research is focused on the advantage of using daily journal writing in teaching recount texts for the second grade students at MTs Khoirotul Islamiyah Pematangsiantar. The problem of this research are: 1) How is the implementation of daily journal writing in teaching recount text for the second grade students at MTs Khoirotul Islamiyah Pematangsiantar? ; 2) What are the advantages of daily journal writing in teaching recount text for the second grade students at MTs Khoirotul Islamiyah Pematangsiantar?. The objective of this study are: 1) To describe the implementation of daily journal writing to teach recount text for second grade at MTs Khoirotul Islamiyah Pematangsiantar; 2) To know what are the advantages of daily journal writing in teaching recount text of second grade at MTs Khoirotul Islamiyah Pematangsiantar. From the data analysis it can be concluded that : 1) Daily journal writing makes the students motivated and interested in making recount text; 2) Using daily journal writing in teaching recount text have many advantages for the teacher and students in learning activities, it is known from the result of obsevation in the classroom, questionnaire, and interview to the English teacher.